2014
DOI: 10.4172/2155-6156.1000322
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Influencing Diabetic Foot Ulcer among Diabetic Patients Attending Arbaminch Hospital, South Ethiopia

Abstract: Background: Diabetic foot ulcer is one of the long standing complications of diabetic mellitus with the life time risk up to 25%. In Africa in general, particularly in Ethiopia, there are limited epidemiological studies related to diabetic foot ulcer. Objective:The main objective of this study is to assess prevalence and factors influencing diabetic foot ulcer among diabetic patients attending Arbaminch hospital. Methods:A cross sectional study was conducted on 216 diabetic clients attending Arbaminch hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 15 publications
7
30
0
1
Order By: Relevance
“…Consistent with this finding, several studies have reported a higher prevalence of DFU in older age groups (7,12,14). Older diabetic patients mostly show a long duration of the disease associated with various diabetes-related complications and other chronic diseases that could explain the higher risk of DFU in older age groups (6,19,20).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with this finding, several studies have reported a higher prevalence of DFU in older age groups (7,12,14). Older diabetic patients mostly show a long duration of the disease associated with various diabetes-related complications and other chronic diseases that could explain the higher risk of DFU in older age groups (6,19,20).…”
Section: Discussionsupporting
confidence: 63%
“…Male patients had significantly higher DFU prevalence than female patients (22.9% vs. 14.6%). A higher DFU frequency was reported in male diabetic patients in several studies (7,12,20). Some studies have shown that men are at greater risk of DFU due to having a higher rate of risk factors leading to DFU such as smoking, peripheral vascular diseases, limited joint mobility, poor glycemic control, and poor medication adherence (7,13,14).…”
Section: Discussionmentioning
confidence: 95%
“…A lifetime risk as high as 15 to 25 % has also been reported [11,12]. The prevalence of DFU among diabetic patients varies widely from about 14.8 % in Ethiopia to 21.2 % in Calabar, Nigeria [13][14][15][16]. In Lagos, Nigeria, Ogbera et al [17] found a high prevalence of 41.5 % for DFU.…”
Section: Introductionmentioning
confidence: 93%
“…In our environment, socioeconomic and sociocultural factors such as poverty, poor hygiene, walking barefooted, and ignorance are issues to contend with also [2,16,24]. Some factors reported to influence the development of DFU include rural residence, presence of comorbidity, duration of diabetes, mean arterial blood pressure, and occupation [13].…”
Section: Introductionmentioning
confidence: 99%
“…23 In different sub-Saharan African countries, the prevalence of DFU ranges from 3.4% to 18.1% [24][25][26][27] and studies conducted in different parts of Ethiopia showed that the prevalence of DFU ranges from 12 to 17.86%. [28][29][30][31] Studies indicated that DFU is affected by sociodemographic factors, clinical factors, and comorbidities. Among socio-demographic factors male sex, 32,33 being in the older age group, [34][35][36] and rural residency 28,31 are related to a higher risk of DFU.…”
Section: Introductionmentioning
confidence: 99%